(untitled) (Bangladesh Journal of Neuroscience, 2013)
Amyotrophic lateral sclerosis (ALS) is a progressive neuromuscular condition characterized by proximal and distal muscle wasting, weakness, fasciculation. The etiology of the disease is unknown. The annual incidence rate is one to two cases per 100,000 persons. The disease is most commonly presents in middle age, mostly after the age of 50 and very uncommon before the age of 30 years and affects men more than women. Usually it present with limb muscle weakness, cramps, occasionally fasciculations and sometimes with dysarthria, dysphagia. Symptoms often begin focally in one part and spread gradually but relentlessly to become widespread. Over a period of months or years, patients with ALS develop severe, progressive muscular weakness and other symptoms caused by loss of function in both upper and lower motor neurons. Sphincter control, sensory function, intellectual abilities and skin integrity are preserved. Patients become completely disabled, often requiring ventilatory support and gastrostomy. Death usually occurs within five years of diagnosis and is attributed to respiratory failure or cachexia. Current management involves aggressive, individualized alleviation of symptoms and complications. We are reporting an 18 year old right handed male presented with typical features of ALS . The purpose for reporting was for its rarity before 40 years and that had a typical clinical features of young-adult ALS, and to compare them with features of the common adult-onset type. Bangladesh Journal of Neuroscience 2013; Vol. 29 (2) : 134-138